LEARNING ANXIETY IN SPEAKING ACTIVITIES AMONG SENIOR HIGH SCHOOL - Cahyaningtiyas, Yola; Hatip, Mochammad; Oktarini, Widya (Unversitas Katolik Santo Thomas, 2025)
In Anxiety in speaking English remains a major obstacle for high school students in the learning process. This study aims to describe the level and type of speaking anxiety experienced by students in the context of English language learning. This study employs a descriptive quantitative approach involving 100 eleventh-grade students at SMAN 1 Asembagus. The instrument used is the Foreign Language Classroom Anxiety Scale (FLCAS), which has been validated and analysed using SPSS version 27. The results indicate that 40% of students are at a low level of anxiety, 55% at a moderate level, and 5% at a high level. The most dominant aspect of anxiety was communication apprehension with an average score of 25.50, followed by fear of negative evaluation (23.22), and test anxiety (12.31). These findings indicate that most students feel anxious when they have to speak spontaneously in English. Therefore, teaching strategies that support and create a comfortable classroom environment are needed to help students feel more confident in speaking English.